How does the Extracellular Matrix Change in the Setting of Heart Failure? - Amerikos Argyriou (University Library System, University of Pittsburgh, 2018)
The Extracellular Matrix is a dynamic entity, showing constant degradation and deposition while providing the framework for the cardiomyocytes and interstitial proteins to lie on. Its function is important for the proper myocyte alignment within the heart and for internal communication from cell to matrix. Dysregulation of the remodeling process resulting in the breakdown of collagen by matrix metalloproteinases is a hallmark of heart failure pathophysiology and produces functional changes encompassing all matrix proteins. Several etiologies with distinct mechanisms ultimately bring about signs of heart exhaustion such as reduced ejection fraction, reduced compliance and ventricular dilatation. Discussed in this paper is the role of inflammation, collagen cross-linking and of myofibroblasts in matrix dysfunction and the mechanisms with which these changes occur in heart failure. Understanding extracellular protein roles within this context would allow for specific drug targeting and thus prevention of heart failure in the early stages of the disease. More studies must be conducted to discover the specific matrix proteins and cytokines that modulate the pathological remodeling process. Serum biomarkers of extracellular degradation products, selective metalloproteinase inhibitors and a personalized treatment approach with a revisal of the current classification of heart failure are topics requiring further exploration.